2019
DOI: 10.1002/mgg3.672
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of serum tumor markers and BRCA1/2 germline mutations in Chinese ovarian cancer patients

Abstract: Background The serum tumor markers has been widely used in ovarian cancer diagnosis. BRCA1/2 germline mutations are the most common predisposing factors for ovarian cancer development. This study aimed to comprehensively investigate serum tumor markers and BRCA1/2 germline mutations and analyze their associations with ovarian cancer. Methods Levels of 11 serum tumor markers were examined in ovarian cancer patients and controls with benign gynecologic diseases. By integrating multiplex PCR and next‐generation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…( 12 , 19 21 ); this is probably caused by the different ethnic origins and geographic locations of the included patients. Several studies have reported the BRCA1 :c.5470_5477del as the most frequently detected mutation in Chinese OC patients; of note, the patients enrolled in these studies were mainly from northern China ( 13 , 20 , 22 ), and studies on the southern Chinese revealed different top mutations ( 12 , 19 , 21 ). In this study, almost all the patients are from Henan, the central region of China and the origin of Chinese civilization.…”
Section: Discussionmentioning
confidence: 99%
“…( 12 , 19 21 ); this is probably caused by the different ethnic origins and geographic locations of the included patients. Several studies have reported the BRCA1 :c.5470_5477del as the most frequently detected mutation in Chinese OC patients; of note, the patients enrolled in these studies were mainly from northern China ( 13 , 20 , 22 ), and studies on the southern Chinese revealed different top mutations ( 12 , 19 , 21 ). In this study, almost all the patients are from Henan, the central region of China and the origin of Chinese civilization.…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous advancement of molecular biology technology, the detection of serum tumour markers has gradually been applied in clinical practice. It has become a milestone in medical science and has safety advantages, non‐invasiveness and simple sampling 19,20 . Carcinoembryonic antigen (CEA), 5 sugar chain antigen 19–9 (CA199) 6 and CA125 7 are commonly used clinical tumour markers and have been proven to have application value in various malignant tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor markers are not only used in screening ovarian cancer; some studies found that CA125 showed good performance in ovarian cancer with BRCA1/2 mutation detection as a single marker (AUC=0.799). 11 This reminded us that tumor markers may represent the characteristics to some degree. Unfortunately, our results suggested that CA125, the most commonly used tumor marker in ovarian cancer, had no significant effect on survival or on the outcomes of PDS.…”
Section: Dovepressmentioning
confidence: 99%